2013
DOI: 10.1074/jbc.m113.511170
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Aberrant Glutathione Metabolism to Eradicate Human Acute Myelogenous Leukemia Cells

Abstract: Background: Eradication of primary human leukemia cells represents a major challenge. Therapies have not substantially changed in over 30 years. Results: Using normal versus leukemia specimens enriched for primitive cells, we document aberrant regulation of glutathione metabolism. Conclusion: Aberrant glutathione metabolism is an intrinsic property of human leukemia cells. Significance: Interventions based on modulation of glutathione metabolism represent a powerful means to improve therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
176
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 173 publications
(200 citation statements)
references
References 60 publications
(64 reference statements)
10
176
1
1
Order By: Relevance
“…CD34 + AML cells were found to have aberrant glutathione metabolism and were sensitive to therapies that further disrupted the glutathione pathway, such as parthenolide and piperlongumine, and it was proposed that AML cells are addicted to glutathione (39). Our results in FLT3-ITD + AML cells support this hypothesis, because FLT3 inhibitors were shown to deplete glutathione, which correlated with increased mitochondrial ROS and the induction of apoptosis.…”
Section: Discussionsupporting
confidence: 78%
“…CD34 + AML cells were found to have aberrant glutathione metabolism and were sensitive to therapies that further disrupted the glutathione pathway, such as parthenolide and piperlongumine, and it was proposed that AML cells are addicted to glutathione (39). Our results in FLT3-ITD + AML cells support this hypothesis, because FLT3 inhibitors were shown to deplete glutathione, which correlated with increased mitochondrial ROS and the induction of apoptosis.…”
Section: Discussionsupporting
confidence: 78%
“…Using LC-MS/MS of each fraction, we subsequently identified 312 binding targets of PTL in primary AML cells (supplemental Table 1). Notably, several previously reported binding targets of PTL including IKK␤, GCLC, GPX1, and TXN were all successfully identified through this approach (25)(26)(27), suggesting our method had good specificity and coverage. Subsequently, we employed the Ingenuity Pathway Analysis (IPA) software and identified a list of pathways/biological functions that are significantly represented by this pool of binding targets (supplemental Table 2).…”
Section: Identification Of the Proteomic Interactome Of Ptl In Primarymentioning
confidence: 89%
“…Although previous studies by our group and others have shown that PTL is a strong inhibitor of the NF-B pathway and also a potent inhibitor of glutathione metabolism (22,(25)(26)(27)(28)(29), there have been very few studies that systematically characterize its anti-cancer mechanism at a multi-omic level. In the present study, we investigated the mechanism of PTL by first using a biotinylated analog to identify its proteomic interactome.…”
mentioning
confidence: 99%
“…Interestingly, this effect was observed in CML CD34 + lin − cells, but not on their normal counterpart. NBM primitive cells showed lower basal levels of ROS than their CML counterpart, this could indicate higher levels of reduced glutathione in normal populations, which would make normal primitive cells resilient to PTL and DMAPT effect as has been observed in CD34+ cells from AML samples,13 and proves a key mechanism to be exploited and further studied. PTL and DMAPT also inhibited phosphorylation and nuclear localization of NF‐κB (p65).…”
Section: Discussionmentioning
confidence: 84%
“…To improve the pharmacological properties of PTL, an orally bioavailable analogue was generated, dimethyl amino parthenolide (DMAPT) that showed similar activity to PTL in AML LSC11; nevertheless, the effect on CML cells, including both primitive primary cells, as well as CML cell lines, is unknown. The mechanism of action of PTL has been reported to rely on a number of pathways, two of which are the inhibition of NF‐κB via the alkylation of critical cysteine residues12 and the induction of ROS by affecting the glutathione system 13…”
Section: Introductionmentioning
confidence: 99%